Does the Package Really Sell? – Pilotage Study - Ratajczyk, Monika (Economic and Environmental Studies, 2020)
Packaging is a significant marketing tool. It plays a vital role in product strategy, but also remains a tool for brand communication with a consumer. Effective packaging should encourage to buy the product, but whether consumers actually pay attention to them? The article presents the results of author’s own research (ethnography) on young consumers (18-26 years) living in Lublin (Eastern Poland) completed in July 2016. In the study, the process of food products purchasing was followed and carried out in the usual manner by a participant (in a shop chosen by him/her) and then approximately a 40minute interview about his/her shopping habits was conducted. The study showed a number of factors that limits the promotional function of a single unit product package. These include: shopping routine, some shopping habits, the specificity of commercial space in a store and an increase of consumer awareness.